PENGARUH KOMPETENSI GURU BAHASA ARAB TERHADAP MOTIVASI BELAJAR BAHASA ARAB SISWA MADRASAH ALIYAH DARUL ARQAM GOMBARA MAKASSAR - Andi Fajriwati Tadjuddin (Universitas Muhammadiyah Makassar, 2017)
This study aims to know in general illustration of the competence of Arabic teachers and the motivation of learning Arabic language students in Madrasah Aliyah Darul Arqam Gombara Makassar, as well as to determine the relationship of Arabic teachers' competence to the learning motivation of Arabic students in Madrasah Aliyah Darul Arqam Gombara. The methods used in this study were qualitative methods with questionnaires, interviews, documentation and observation. The results of this study indicated that a competent teacher could influence the students' learning motivation so as to improve student achievement. Conversely, if the teacher was not competent, then students would be reluctant to learn because it was not balanced with the motivation to learn so as not to obtain maximum performance. In this study, students' interests play more dominant roles in improving learning achievement than teacher competence. Although the competence of teachers also had a big role, but without any encouragement or desire from within the students, the achievements would be less satisfactory. But there were many factors that influence the success of students in improving learning achievement. Thus the success of students in achievement was not only determined by the competence of teachers and learning motivation, but also there were many internal or external factors that could affect the learning outcomes of each student. Keywords: competence, teacher, motivation, learning